Efficiency and Profitability in The Indonesian Islamic Banking Industry - Muhammad Nadratuzaman Hosen; Rafika Rahmawati (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2016)
The aims of this study are to know the level of efficiency and profitabilityamong Islamic full pledge Banks in Indonesia. Using parametric approach namelyStochastic Frontier Approach (SFA) to calculate efficiency and using ROA’s ratioto calculate profitability. The result showed that the BMS was the greatest level ofefficiency among Islamic Banks in Indonesia which influence the input and outputlevel of efficiency of BMS are personnel expenses, cost-sharing expenses, and totalfinancing which owned. Besides, the result showed that it was the greatest levelof profitability which factors influencing of profitability of BMS is BOPO’s ratio.The result also showed that the BMI had low efficiency but sufficient profitability.It has sufficient efficiency and high profitability, the BMS have sufficient efficiencyand profitability, the BRIS have low efficiency and profitability, and the BSB havehigh efficiency and low profitability.DOI: 10.15408/aiq.v8i1.2507